Influence of Harvesting and Processing Methods on the Active Principles of Medicinal Plants - Pushpan, Reshmi (International Journal of Pharmaceutical & Biological Archive, 2013)
Influence of Harvesting and Processing Methods on the Active Principles of Medicinal Plants